Characterization of mechanical and physical properties of eggshell waste by using cold compaction - Wahab, Mohd Daniel; Mohamad, Zaleha (FAZ Publishing, 2020)
Utilization of eggshell waste is a significant solution to reduce environmental problems. The aim of this research is to study the potential of eggshell waste as water filter. Eggshell waste (ESW) is the primary material that has been used in this research. Both types of binder which are kaolin clay and wheat flour were added to the eggshell waste. Different composition of eggshell powder (ESP) (20%, 30%, 40%, 50%), kaolin clay (10%, 20%, 30%, 40%) and 40% fixed of wheat flour were prepared. The mechanical and physical properties of eggshell waste were analysed through compressive test, turbidity test, density test and porosity test. Both mechanical and physical tests are followed American Society for Testing and Material (ASTM). The loading rate for compressive test was 1.5mm/min following ASTM B939 with samples size of 25mm x 5mm. Meanwhile for porosity and density test were followed ASTM C642 and B962. Based on comparison results, the addition of eggshell powder has increased the compressive strength of the tested material. The result from turbidity test exhibits that the level of turbidity decrease when added eggshell into the waste water. The porous structure of the eggshell has influenced the absorption of contaminants from the waste water